Identifikasi lansekap pura Negara Gambur Anglayang di Desa Kubutambahan, Kecamatan Kubutambahan, Kabupaten Buleleng - Samba, I Gede Bagus Reza Widiarsa; Semarajaya, Cokorda Gede Alit; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap; Vol.4, No.2, Oktober 2018, 2018)
Identification of Negara Gambur Anglayang temple landscape on Kubutambahan Village, Kubutambahan Subdistrict, Buleleng Regency. Negara Gambur Anglayang Temple is one of the temples located in Kubutambahan Village, Buleleng Regency. There are some type of monument in this tample like monument Ratu Bagus Sundawan as an element Sunda, monument Ratu Agung Melayu as an element Melayu, monument Ratu Agung Syahbandar as an element China/Budha, monument Batara Surya, monument Ratu Pasek, monument Dewi Sri, monument Ratu Gede Siwa as an element Hindu/Bali, dan monument Ratu Gede Dalem Mekah as an element Islam. Identification of spatial pattern and forming elements of Negara Gambur Anglayang Temple is to find out whether the existence of various monument will influence the pattern of space used. The method used in this research is survey method, with data collection techniques is observation, interview, and literature. The results showed that the temple forming elements consisted of plants as soft elements and buildings as hard elements with their respective functions. The layout of the existing plants in the temple does not use the concept of Balinese cultural philosophy, and for the layout of the building using the concept of Balinese cultural philosophy that is hulu-teben. Spatial pattern used in Negara Gambur Anglayang Temple is Tri Mandala, where the part of yard is divided into three namely Nista Mandala, Madya Mandala and Utama Mandala.